Effects of inactivation of the cyAbrB2 transcription factor together with glycogen synthesis on cellular metabolism and free fatty acid production in the cyanobacterium Synechocystis sp. PCC 6803. Issue 12 (8th November 2018) - Kodama, Yuta; Kawahara, Akihito; Miyagi, Atsuko; Ishikawa, Toshiki; Kawai‐Yamada, Maki; Kaneko, Yasuko; Takimura, Yasushi; Hihara, Yukako
Abstract: Deletion of the cyAbrB2 (Sll0822) transcription factor in Synechocystis sp. PCC 6803 causes aberrant accumulation of glycogen. We previously tried to redirect the excess carbon stored as glycogen in the cyabrB2 ‐disrupted (∆ cyabrB2 ) mutant by knockout of the glgC (slr1176) gene encoding glucose‐1‐phosphate adenylyltransferase. However, complete knockout could not be attained, suggesting that accumulation of glycogen is essential for the Δ cyabrB2 mutant. In this study, we introduced the cyabrB2 gene fused to the copper‐inducible petE promoter into the ∆ cyabrB2 mutant. After complete knockout of glgC in the presence of copper, expression of P petE ‐ cyabrB2 was turned off by copper removal to examine the effect of the double knockout of cyabrB2 and glgC . Metabolome analysis and electron microscopic observation revealed that the double knockout causes a large decrease of sugar phosphates in glycolytic and oxidative pentose phosphate pathways and an increase of organic acids in the tricarboxylic acid cycle, amino acids and storage compounds such as polyhydroxybutyrate. When the ability of production of free fatty acids was conferred, synergetic positive effects of knockout of cyabrB2 and glgC on productivity were observed by removal of both copper and nitrogen. The P petE ‐ cyabrB2 Δ glgC strain will further serve as a platform for studies on carbon allocation and metabolic engineering. Abstract : Deletion of the cyAbrB2 transcription factor in Synechocystis sp. PCC 6803 causes aberrant accumulation of glycogen. By using copper‐inducible switching strain PpetE‐cyabrB2, we examined the effects of double knockout of cyabrB2 and the glgC gene working for glycogen synthesis. The double knockout causes large decrease of sugar phosphates and increase of organic acids, amino acids and storage compounds. When free fatty acids‐producing strains were made by introduction of aas::UcTE, synergetic positive effects of knockout of cyabrB2 and glgC were observed.